2014
DOI: 10.3390/v6114358
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Glycoprotein G Antibodies of Herpes Simplex Virus 2 Contribute to Complete Protection after Vaccination in Mice and Induce Antibody-Dependent Cellular Cytotoxicity and Complement-Mediated Cytolysis

Abstract: We investigated the role of antibodies against the mature portion of glycoprotein G (mgG-2) of herpes simplex virus 2 (HSV-2) in protective immunity after vaccination. Mice were immunized intramuscularly with mgG-2 and oligodeoxynucleotides containing two CpG motifs plus alum as adjuvant. All C57BL/6 mice survived and presented no genital or systemic disease. High levels of immunoglobulin G subclass 1 (IgG1) and IgG2 antibodies were detected and re-stimulated splenic CD4+ T cells proliferated and produced IFN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Initially we compared the intramuscular immunizations with the subcutaneous + intranasal immunizations showing that the intramuscular protocol was significantly better. Similarly, in our earlier report, using mgG-2 as vaccine antigen, the intramuscular administration induced significantly higher survival rate, lower disease scores and higher IgG1, IgG2b and IgG2c antibody levels [ 28 ]. The molecular mechanisms behind these differences are to our knowledge unclear.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Initially we compared the intramuscular immunizations with the subcutaneous + intranasal immunizations showing that the intramuscular protocol was significantly better. Similarly, in our earlier report, using mgG-2 as vaccine antigen, the intramuscular administration induced significantly higher survival rate, lower disease scores and higher IgG1, IgG2b and IgG2c antibody levels [ 28 ]. The molecular mechanisms behind these differences are to our knowledge unclear.…”
Section: Discussionsupporting
confidence: 63%
“…This i.m. protocol was chosen as it has successfully been used in an earlier report using mgG-2 as immunization antigen [ 28 ]. The control groups were immunized with sgG-2 protein without adjuvant, with CpG and alum alone, or with phosphate buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%
“…Recent research with both HIV and HSV has shown that ADCC can be directed against non-neutralizing viral antigen targets [37]. Furthermore, this research has suggested that ADCC may be important for prevention of HSV reactivation as well as clearance of HIV infected T lymphocytes [3840]. Currently, there is no published research examining the role of ADCC in the clearance of PRRSV from infected macrophages.…”
Section: Non-neutralizing Antibody Functions Against Prrsvmentioning
confidence: 99%
“…Mice were intramuscularly immunized with eukaryotic expression plasmids encoding gD to induce protective immune responses (17)(18)(19). Certain immune adjuvants such as interleukin-12, chemokines, cytokines and the E. coli heat labile enterotoxin can enhance the immunogenicity of the HSV DNA vaccine (20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%